Altered Expression of Phox2 Transcription Factors in the Locus Coeruleus in Major Depressive Disorder Mimicked by Chronic Stress and Corticosterone Treatment In Vivo and In Vitro - Fan, Yan; Chen, Ping; Raza, Muhammad U.; Szebeni, Attila; Szebeni, Katalin; Ordway, Gregory A.; Stockmeier, Craig A.; Zhu, Meng-Yang (Neuroscience, 2018)
[Display omitted] •Protein levels of Phox2a, mRNA and protein levels of Phox2b were elevated in the locus coeruleus from brain donors of MDD.•CSD significantly increased Phox2a and Phox2b expression in the rat locus coeruleus.•Corticosterone administration increased Phox2b protein levels in the rat locus coeruleus.•Corticosterone increased Phox2a and Phox2b expression in the SK-SY5Y cells.•Corticosterone-induced increase in Phox2 expression may be mediated through corticosteroid receptors. Phox2a and Phox2b are two homeodomain transcription factors playing a pivotal role in the development of noradrenergic neurons during the embryonic period. However, their expression and function in adulthood remain to be elucidated. Using human postmortem brain tissues, rat stress models and cultured cells, this study aimed to examine the alteration of Phox2a and Phox2b expression. The results show that Phox2a and Phox2b are normally expressed in the human locus coeruleus (LC) in adulthood. Furthermore, the levels of Phox2a protein and mRNA and protein levels of Phox2b were significantly elevated in the LC of brain donors that suffered from the major depressive disorder, as compared to age-matched and psychiatrically normal control donors. Fischer 344 rats subjected to chronic social defeat showed higher mRNA and protein levels of Phox2a and Phox2b in the LC, as compared to non-stressed control rats. In rats chronically administered oral corticosterone, mRNA and protein levels of Phox2b, but not Phox2a, in the LC were significantly increased. In addition, the corticosterone-induced increase in Phox2b protein was reversed by simultaneous treatment with either mifepristone or spironolactone. Exposing SH-SY5Y cells to corticosterone significantly increased expression of Phox2a and Phox2b, which was blocked by corticosteroid receptor antagonists. Taken together, these experiments reveal that Phox2 genes are expressed throughout the lifetime in the LC of humans and Fischer 344 rats. Alterations in their expression may play a role in major depressive disorder and possibly other stress-related disorders through their modulatory effects on the noradrenergic phenotype.